Select Dietary Fibers Alter GI Microbiome Composition & Promote Fermentative Metabolism in the Lower Gastrointestinal Tract of Healthy Adult Dogs (P20-044-19). (13th June 2019) - Fritsch, Dale; Wernimont, Susan; Jackson, Matthew; Badri, Dayakar; Cochrane, Chun-Yen; Gross, Kathy
Abstract: Objectives: The canine gastrointestinal (GI) microbiome is capable of fermenting fibers. We evaluated select dietary plant fibers on canine GI microbiome composition & metabolism. Methods: 39 adult dogs were fed a control food (CF) for 4 weeks, then fed a test food (TF) for 4 weeks. (CF: 3411 kcals/kg, 2.2 g total dietary fiber, TDF; 0.5 g soluble fiber, SF; 1.7 g insoluble fiber, INSF per 100 kcal; TF: 3273 kcal/kg, 5.0 g TDF, 0.8 g SF, 4.2 g INSF per 100 kcal). Foods were complete & balanced dry foods & met 2017 AAFCO nutritional guidelines. CF fiber sources: cracked pearled barley, whole corn, whole grain oats, cellulose; TF: cracked pearled barley, whole corn, whole grain oats, ground pecan shells, cellulose, flaxseed, dried beet pulp, dried citrus pulp, pressed cranberries, dried pumpkin, psyllium seed husks, & ginger root. Feces were collected after 4 weeks of feeding CF and TF, homogenized, & frozen at −80C within 1 hour of defecation. Fecal microbiome 16 s rRNA sequencing was performed using Illumina MiSeq and processed through Mothur. Predicted microbial functions were determined by PICRUSt and analyzed using PERMANOVA. Count-normalized data were CLR transformed & analyzed using negative binomial mixed models. Fecal short chain fatty acids (SCFA) were analyzed using liquid-liquid extraction & gas chromatography with flame ionization detection. Results significant at P  < 0.05 are reported. The study was reviewed & approved by the Institutional Animal Care & Use Committee, Hill's Pet Nutrition, Inc. Dogs had access to clean fresh water at all times. Results: TF significantly increased fecal acetic acid, decreased putrefactive metabolites such as isobutyric, 2-methylbutyric, & isovaleric acids. The acetate-& lactate-producing genera Bacteroides and Faecalibacterium were significantly increased while Streptococus and Enterococcus were significantly decreased vs CF. Predicted microbial functions representing butyrate, phenylalanine & tyrosine metabolic pathways were significantly different from CF. Conclusions: TF shifts canine GI microbiome composition and metabolism toward saccharolytic fermentation & decreases putrefactive metabolites, characteristics which provide beneficial impacts to canine GI health. Funding Sources: This study was funded by Hill's Pet Nutrition, Inc.